Assessment policy of post-traumatic stress disorder in aviation and its practical application using turbulence-triggered trauma as an example - Vuorio, Alpo; Bor, Robert; Budowle, Bruce; Gray, Alastair; Suhonen-Malm, Anna-Stina (Frontiers in Public Health, 2025)
The U.S. Federal Aviation Administration (FAA) recently provided detailed instructions on how Aviation Medical Examiners (AMEs) should assess and evaluate pilots for post-traumatic stress disorder (PTSD). The European, Australian and International Civil Aviation Organization guidelines for the assessment of PTSD in aviation are general guidelines and do not address the unique and specific circumstances of a flight crew per se. The starting point of the U.S. FAA’s guidance is an already-established clinical PTSD diagnosis since it is known that PTSD compromises aviation safety and has been related to fatal aviation accidents. According to the FAA’s guidance, a PTSD assessment is undertaken based on whether the condition is symptomatic and medicated, or whether more than 2 years have elapsed since showing symptoms and receiving medication. The International Classification of Diseases (ICD) criteria for stress disorders have changed between versions ICD-10 and the soon-to-be-released ICD-11. The new ICD-11 criteria are discussed in this article in the context of aviation health. Additionally, PTSD, potentially caused by an incident of turbulence, is discussed in the context of aviation mental health. There are currently no published studies on turbulence-caused mental trauma. We have identified in this article potential factors which are related to pilots’ and cabin crew’s stressors in incidents of severe and extreme turbulence. Three recommendations are provided: (1) harmonize assessment practices of PTSD internationally; (2) healthcare professionals taking care of traumatized flight crew should have a follow-up guide that takes specific and local conditions into account, and ensures the identification of patients who require follow-up treatment as early as possible; and (3) aviation health care professionals should consider ICD-11 diagnostic criteria as the information may be more useful in the assessment and diagnosis of aviation-related trauma.